Service Providers’ Attitudes Toward Mandatory Reporting of Intimate Partner Violence: The Impact of Professional Experience - Nordby, Christine (Journal of interpersonal violence, 2025)
Mandatory reporting (MR) among service providers (SP) working with intimate partner violence (IPV) is controversial, and the research is scarce. The potential association of SPs experience with IPV and MR-IPV and their attitudes is the aim of the current study. A total of 374 SPs working with victims and perpetrators (help-seekers) of IPV participated in this study. Factor analysis was conducted to produce a continuous standardized dependent variable as a measure of attitudes toward MR-IPV. Descriptive results indicated that SPs were generally supportive of MR-IPV. Linear regression analyses showed that a higher degree of professional experience with IPV was significantly associated with less skepticism of MR-IPV. The result was significant regardless of (1) severity of violence, (2) category of help-seeker, (3) time of incidents, and (4) number of cases where MR-IPV was considered relevant. Having substantial experience with IPV and MR-IPV remained significant adjusting for the SP category, years in current position, knowledge of MR, and frequency of mandatory reports. Our results indicate that experience is an important part of SPs attitudes toward MR-IPV.